2019
DOI: 10.4183/aeb.2019.247
|View full text |Cite
|
Sign up to set email alerts
|

From Diabetes Insipidus to Sellar Xanthogranuloma – a “Yellow Brick Road” Demanding Team-Work

Abstract: Xanthogranulomas are inflammatory lesions exceptionally rarely occurring in the sellar region. Sellar xanthogranulomas (SXG) result from secondary hemorrhage, infarction, inflammation or necrosis upon existing craniopharyngioma (CP), Rathke`s cleft cyst (RCC) or pituitary adenoma (PA), or represent a stage in xanthomatous hypophysitis evolution. "Pure SXG" are independent of a preexisting lesion. A 70 year old male patient, laryngeal cancer survivor, presented with central diabetes insipidus (CDI). MRI reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Ved et al reported it in only one of their 6 cases with pituitary XG, while Hernandez-Estrada et al reported AVP deficiency, at presentation, in 6 out of 27 patients (22.2%) [7,15]. Our patient who presented with AVP deficiency, was published previously, with review of the literature including 10 cases of sellar XG presenting with AVP deficiency, as an infrequent presenting feature [22].…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 48%
See 1 more Smart Citation
“…Ved et al reported it in only one of their 6 cases with pituitary XG, while Hernandez-Estrada et al reported AVP deficiency, at presentation, in 6 out of 27 patients (22.2%) [7,15]. Our patient who presented with AVP deficiency, was published previously, with review of the literature including 10 cases of sellar XG presenting with AVP deficiency, as an infrequent presenting feature [22].…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 48%
“…Presence of epithelium in patients with primary forms of XG, lacking the other components of a cystic pituitary lesion or CP, was observed in one of our patients reported previously by us and other authors [2,17,22]. The origin of traces of epithelium, which can be found in some patients with primary XG is intriguing and described in <10% of patients [9].…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 51%
“…Observations Xanthomatous lesions of the pituitary gland are a rare category of hypophysitis that have been described in several reports. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Traditionally, these lesions have been divided into two distinct categories: XH and XG; however, there is growing evidence of clinicopathologic overlap between them. 3 XH is histologically characterized by the presence of foamy histiocytes and lymphoplasmacytic infiltrates within the pituitary gland or sellar region with little to no hemosiderin pigment.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7 When recurrence does happen, many patients either undergo repeat resection or are treated with high-dose corticosteroids with varying results. [8][9][10][11][12] We report a case of an adolescent male found to have RCC with a postoperative course complicated by recurrent XGH. He experienced complete resolution of the inflammatory reaction on a short course of dexamethasone followed by a maintenance course of celecoxib and mycophenolate mofetil (MMF).…”
mentioning
confidence: 99%
“…In immunohistochemistry, the epithelium is positive for cytokeratins (usually CK7, exceedingly CK20) and negative for S-100 and Synaptophysin (Figure 5) (40). The differential diagnosis between Rathke cleft cysts and craniopharyngiomas might be challenging and demands a detailed correlation between pathological, endocrinological, neurosurgical and neuroradiological findings (41). Regarding papillary craniopharyngioma, it could be overcome by the use of BRAF V600E antibody, since its immunohistochemical positivity is observed in papillary craniopharyngioma, in contrast to the epithelium of Rathke cleft cyst, where it is negative (42).…”
Section: Rathke Cleft Cystmentioning
confidence: 99%